Trends in the professional training of railway electrical engineers of railway transport - D. O. Belov (Вестник Самарского университета: История, педагогика, филология, 2021)
The article deals with the main trends in the professional training of railway electrical engineers, which determine the relations between railway universities and production. The trend of integration due to the unification of the content of education and the determinism of academic disciplines ensures the professional mobility of a specialist both within the profession and in related areas of production. Teaching at a sufficiently high level of difficulty, stimulating the active cognitive and creative activity of students, requires an intensification trend due to the compaction and increasing volumes of information flows, the rapid development of the technical and technological foundations of production. The trend of cooperation determines the main directions and forms of interaction of vocational training with production and other institutions of higher vocational education. The gradual development of the main functions of professional activity (production and technological, operational and managerial, administrative and regulatory), in the process of personnel development of railway electrification engineers, contributing to the progressive development of specialist competencies, increases the adaptation period to the conditions of professional activity, characterized by the complex impact of professional risks. The study of the experience of professional training of railway transport specialists revealed the need for the formation of professional and personal characteristics of railway electrical engineers, which ensure the reduction of the impact of professional risks set by the factors of danger, uncertainty and alternativeness.